2020
DOI: 10.3389/fonc.2020.548867
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Response of EGFR- and HER2-Amplified Metastatic Colon Cancer to Pyrotinib After Failed Multiline Treatments: A Case Report and Literature Review

Abstract: Human epidermal growth factor receptor 2 (HER2) has been verified as a valuable biomarker and treatment target in metastatic colorectal cancer (mCRC). Pyrotinib, a novel irreversible HER2/epidermal growth factor receptor (EGFR) dual tyrosine kinase inhibitor, can efficiently inhibit the proliferation of HER2-positive cancer cells in many tumors. We report a case of a 40-year-old woman with both HER2-and EGFR-amplified metastatic colon cancer, who developed refractory disease resistant to multiline therapies (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Pyrotinib, an irreversible pan-HER TKI targeting HER2, EGFR, and HER4, was approved in China in 2018 for the treatment of HER2-positive recurrent or metastatic breast cancer and has shown anti-tumor effects in other solid tumors such as lung and gastric cancers[ 79 ]. Li et al [ 80 ] found that pyrotinib monotherapy could be effectively used for salvage therapy in HER2-amplified mCRC patients who have developed resistance to trastuzumab and lapatinib (Tykerb), based on which Chang et al [ 81 ] conducted the HER2-FUSCC-G study. HER2-FUSCC-G is a single-center open-label, non-randomized, ongoing, phase II study with three cohorts to evaluate the efficacy of pyrotinib in patients with HER2-positive gastrointestinal cancer refractory to standard treatment.…”
Section: Her-2-amplified Mcrcmentioning
confidence: 99%
“…Pyrotinib, an irreversible pan-HER TKI targeting HER2, EGFR, and HER4, was approved in China in 2018 for the treatment of HER2-positive recurrent or metastatic breast cancer and has shown anti-tumor effects in other solid tumors such as lung and gastric cancers[ 79 ]. Li et al [ 80 ] found that pyrotinib monotherapy could be effectively used for salvage therapy in HER2-amplified mCRC patients who have developed resistance to trastuzumab and lapatinib (Tykerb), based on which Chang et al [ 81 ] conducted the HER2-FUSCC-G study. HER2-FUSCC-G is a single-center open-label, non-randomized, ongoing, phase II study with three cohorts to evaluate the efficacy of pyrotinib in patients with HER2-positive gastrointestinal cancer refractory to standard treatment.…”
Section: Her-2-amplified Mcrcmentioning
confidence: 99%
“…Multiple clinical trials focusing on HER2-targeted therapies have resulted in exciting outcomes in the treatment of various solid tumors with abnormal expressions of HER2 [9][10][11]. As a robust irreversible EGFR/HER2 dual tyrosine kinase inhibitor, pyrotinib has shown remarkable responses in many advanced cancers even with previously failed EGFR/HER2 targeted treatments [12,13]. Therefore, it is worth exploring whether pyrotinib has the equivalent e cacy in advanced OSCC.…”
mentioning
confidence: 99%